Pembekalan Penggunaan Software dan Pemahaman Teknologi Untuk Perangkat Desa Di Desa Pasirukem - Yana Cahyana (Jurnal Ilmiah Pangabdhi, 2021)
In order to improve the quality of Human Resources (HR) who worked in the village, training in the use of software is considered important because government programs sometimes only extend to the district or sub-district level. This service activity was entitled Provision of Software Use and Technology Understanding for village officials in Pasirukeum Village, Karawang Regency, West Java Province. The purpose of this training is to be able to provide increased capacity in the use of technology for village officials. Another goal is to provide an understanding of technology that village officials deem necessary to know, especially during the Covid-19 pandemic, so that it is hoped that it can help village officials in efforts to improve the quality of their performance. The method used during the training is the lecture-discussion method by providing basic software exercises that can be used by village officials. This training has succeeded in providing solutions to existing problems by introducing and providing information related to the use of software such as Zoom Meeting Cloud, Google Meet, Microsoft Word, and Microsoft Excel.